Staging and wintering goose populations in South Sweden 1977-78 to 1986-87 - Nilsson, Leif (Wildfowl, 1988)
A decade of intensive goose counts in south Sweden from 1977 is summarised. The information relates especially to the Bean Goose Anser fabalis with 37-60,000 birds. The smaller numbers of White-fronted Geese A. albifrons, generally around 2,600 are also well covered. Data for other species are less satisfactory.